(untitled) (International Journal of Economics Management and Social Science, 2025)
Sustainable finance has become a significant focus in Indonesia’s financial sector, aligning economic growth with environmental and social objectives. This narrative review examines the development of sustainable finance in the Indonesian stock market through four key pillars: green products, green services, green financing, and green investment. We highlight government policy developments – including the Financial Services Authority’s (OJK) landmark regulations (POJK 51/2017 and POJK 60/2017), the Indonesian Sustainable Finance Roadmap, and the Indonesia Taxonomy for Sustainable Finance (TKBI) – which have laid the groundwork for integrating Environmental, Social, and Governance (ESG) principles. We also explore the introduction of ESG stock indices (such as SRI-KEHATI and the IDX ESG series) and the launch of a carbon trading exchange (IDXCarbon) as new market mechanisms. Furthermore, we discuss corporate responses to these initiatives, such as mandatory sustainability reporting and green bond issuance, and the reaction of investors through ESG-driven investment strategies. Our findings indicate that Indonesia has made notable progress, becoming a regional leader in green finance, though challenges remain in fully aligning financial practices with sustainability goals. We conclude with an overview of the current state of sustainable finance in Indonesia’s capital market and suggestions for future improvements.